2017
DOI: 10.15587/2519-4852.2017.104438
|View full text |Cite
|
Sign up to set email alerts
|

Wood anemone. Anemone Nemorosa L. Analytical review

Abstract: Проаналізовано літературні джерела та узагальнено дані щодо ареалу, вмісту біологічно активних спо-лук та спектру використання у фармації та медицині Anemone nemorosa. Anemone nemorosa -багаторічна трав'яниста рослина з родини жовтецевих (Ranunculaceae). Рослина неофіцинальна, широко застосовується народною медициною як протипухлинний, протизапальний, спа-змолітичний, седативний, потогінний, бактерицидний, протимікробний, протигрибковий, відхаркуваль-ний, діуретичний

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…They are toxic substances that are unfavorable, when consumed, for the growth of soil fauna, because the interaction with tannins makes the litter protein less bioavailable to the soil fauna. Plants, such as Anemone nemorosa (an indicator species of ancient temperate forests), contain glycosides which increase the water-solubility of compounds such as phenols: Lukianchuk et al. (2017) reported that tannins (examples of phenolics) usually cause toxic reactions in some detritivores.…”
Section: Discussionmentioning
confidence: 99%
“…They are toxic substances that are unfavorable, when consumed, for the growth of soil fauna, because the interaction with tannins makes the litter protein less bioavailable to the soil fauna. Plants, such as Anemone nemorosa (an indicator species of ancient temperate forests), contain glycosides which increase the water-solubility of compounds such as phenols: Lukianchuk et al. (2017) reported that tannins (examples of phenolics) usually cause toxic reactions in some detritivores.…”
Section: Discussionmentioning
confidence: 99%
“…Рослини роду Сон (Pulsatilla) характеризуються вмістом широкого спектра біологічно важливих та активних органічних сполук: тритерпеноїди, сапоніни, стероїди, лактони, цукри та алкалоїди [3,4]. В науковій літературі зустрічаються дані щодо використання вищезгаданих рослин в народній медицині та гомеопатії [5,6]. У роботі досліджено гостру токсичність та протизапальну (антиексудативну) активність спиртових екстрактів сну білого (Pulsatila alba).…”
Section: анотаціяunclassified
“…The test compounds selected are oleuropein and ligstroside aglycones, oleacein, oleocanthal, tyrosol, elenolic acid, luteolin, apigenin, pinoresinol, lariciresinol, isolariciresinol, verbascoside, o -coumaric acid and vanillic acid from extra-virgin olive oil [ 8 ], and the main dietary lignans namely matairesinol, secoisolariciresinol, pinoresinol, lariciresinol, medioresinol and syringaresinol [ 5 , 6 , 7 ]. Studies were done in comparison with anemonin, another very active neuroprotective and antitumor [ 26 , 27 , 28 , 29 ] symmetrical plant molecule, also composed of two identical monomers. In silico studies are completed with in vitro studies, punctuated with an evaluation of the cytotoxic and anti-proliferative activity of two ethanolic extracts from fresh and dried Anemone nemorosa L. aerial part ( herba et flores ), on normal and tumor human brain cells, on normal human astrocytes NHA and human glioma cell line U87, respectively.…”
Section: Introductionmentioning
confidence: 99%